Use and duration of antibiotic therapy in acute pulmonary exacerbation of cystic fibrosis: an as yet undefined issue - Lozada-Martinez, Ivan D. (2022)
Cystic fibrosis is a condition about which not much is yet known and remains a hot topic in translational and pulmonary medicine. Evidence on the management of exacerbations is limited, with few clinical trials and systematic reviews. For example, the use and duration of antibiotics in this condition is unknown. Considering that this is a disease that entails high health costs and substantially decreases the functional capacity of the affected person, it is necessary to quickly establish practical algorithms based on evidence. Based on the above, the objective of this narrative review is to synthesize evidence on the use and duration of antibiotic therapy in acute pulmonary exacerbations in patients with cystic fibrosis. For this, a bibliographic search was carried out in the search engines and databases PubMed, ScienceDirect, Embase, EBSCO and MEDLINE. It was defined that any article related to the evaluation of the use and duration of antibiotic therapy in acute pulmonary exacerbation in patients with cystic fibrosis would be included, giving priority to original studies and systematic reviews and meta-analyses. After the review of the title and the summary of all the results, 42 articles were finally included. It was found that antibiotic therapy 10 days after standard treatment, by intravenous route, either doxycycline or azithromycin plus colistimethate, allows greater recovery of lost pulmonary function, lengthens the time until the next exacerbation and resolves symptoms quickly.